Mechanical Properties Analysis of an Al-Mg Alloy Connecting Rod with Submicrometric Structure. (2015) - Fuertes, J.P.; Murillo, O.; León, J.; Luis, C.; Salcedo, D.; Puertas, I.; Luri, R.
Abstract: In spite of the fact that SPD processes considerably improve the mechanical properties of the thus processed materials, in a large number of cases, it is necessary the subsequent employment of a traditional manufacturing process, such as a forging process, in order to obtain the final shape of a specific part. Thus, in general, it is necessary to use a thermal treatment for the material before it is forged. In this research work, the measurement of the mechanical properties of an isothermally forged connecting rod is to carried out. The results obtained for an AA5754 aluminium alloy are to be compared in the case of two different starting states: after an annealing heat treatment and after having been previously ECAP deformed. It is observed an increase of 21% in the HV microhardness in relation to that attained in the connecting rod forged from the material without previous ECAP deformation.